Exempla starotestamentalnych kobiet w interpretacji "Prima Clementis" - Turek, Waldemar (Vox Patrum, 2016)
Some scholars have recently tried to show that the problems in the Christian community at Corinth were caused in a particular way by women wishing to have a more significant role within the community, and that the primary purpose of Saint Clement’s Letter to the Corinthians was to bring them to order and to show them their proper place in the community’s life and activity. The current study primarily tries to show that Prima Clementis was addressed to the entire Corinthian community. This is followed by an analysis of the passages in which Saint Clement presents the feminine figures of the Old Testament: Miriam (the sister of Moses and Aaron), Lot’s wife, Rahab, Judith, and Esther, and interprets them in the context of the Christian situation at Corinth. In this way, it is shown that Clement, by using the exempla method, creates the image of a perfect, ordered, and harmonious community in which women are outstanding for their strong faith, love, and hospitality.